16/#430 Phase 2 results of relacorilant + nab-paclitaxel in patients with recurrent, platinum-resistant ovarian cancer with and without prior bevacizumab. (4th December 2022) - Colombo, Nicoletta; Gorp, Toon Van; Matulonis, Ursula; Oaknin, Ana; Grisham, Rachel; Fleming, Gini; Olawaiye, Alexander; Tudor, Iulia Cristina; Pashova, Hristina; Lorusso, Domenica
Abstract : Objectives: Single-agent chemotherapy is a mainstay of platinum-resistant ovarian cancer treatment. However, most patients eventually face chemotherapy resistance, which might be driven by endogenous cortisol suppressing apoptotic pathways utilized by chemotherapies. A phase 2 study of nab-paclitaxel (NP) with/without the glucocorticoid receptor modulator relacorilant (RELA) in patients with ovarian cancer showed improved progression-free survival (PFS), overall survival (OS), and duration of response (DOR) with addition of RELA. We present a post-hoc subgroup analysis in patients with/without prior bevacizumab. Methods: 178 women with recurrent, platinum-resistant/refractory ovarian, primary peritoneal, or fallopian tube cancer or ovarian carcinosarcoma with ≤4 prior lines of chemotherapy (105 with; 73 without prior bevacizumab) were enrolled in a phase 2, open-label, randomized study (NCT03776812 ). Data for patients receiving either NP (80 mg/m 2 ) + intermittent RELA (150 mg QD the day before, of, and after NP) (n=60) or NP alone (100 mg/m 2 ) (n=60) are reported. Results: Baseline characteristics in the 2 groups were generally balanced. While patients without prior bevacizumab were balanced between North America and Europe, 70% of patients who received prior bevacizumab were in Europe. PFS, OS, ORR, and DOR are shown in table 1 . Conclusions: In this subgroup analysis, patients who had received prior bevacizumab had better PFS, OS, and DOR with intermittent RELA+NP vs NP alone, while ORR was similar across all groups. Numerical improvement in PFS was seen in patients without prior bevacizumab. Prior bevacizumab will be a stratification factor in the phase 3 trial of RELA+NP (ROSELLA, NCT05257408 ) that is planned to start in mid-2022.